2001
DOI: 10.1016/s0002-9440(10)61729-4
|View full text |Cite
|
Sign up to set email alerts
|

Normal and Malignant Prostate Epithelial Cells Differ in Their Response to Hepatocyte Growth Factor/Scatter Factor

Abstract: Hepatocyte growth factor/scatter factor (HGF/SF) promotes the proliferation, differentiation, motility, and invasion of epithelial cells by binding to its cell surface receptor, the Met tyrosine kinase. In the prostate, Met is expressed predominantly by prostate epithelial cells (PrEC), whereas HGF/SF is synthesized by prostate stromal cells (PrSCHepatocyte growth factor/scatter factor (HGF/SF) 1,2 has been implicated in the communication between stromal and epithelial cells of many different organs. HGF/SF is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0
4

Year Published

2003
2003
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 66 publications
2
81
0
4
Order By: Relevance
“…Recently, others have reported that HGF enhances the in vitro attachment to and subsequent invasion through Matrigel of DU145 and PC-3 human CaP cells [34][35][36]. It has also been shown that the serum level of HGF in men with metastatic CaP is significantly elevated compared to men with localized disease [37].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, others have reported that HGF enhances the in vitro attachment to and subsequent invasion through Matrigel of DU145 and PC-3 human CaP cells [34][35][36]. It has also been shown that the serum level of HGF in men with metastatic CaP is significantly elevated compared to men with localized disease [37].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings suggested that the growth stimulants produced by CAFs in lung tumor promoted the proliferation of lung cancer cells in a paracrine manner. Furthermore, other reports have shown that growth factors and angiogenic factors, such as HGF, FGFs and VEGF, were induced or up-regulated in CAFs and that the up-regulation promoted proliferation and progression of cancer cells (34)(35)(36)(37)(38). Conversely, paracrine stimulation by PDGFs secreted from cancer cells has been shown to induce CAFs in tumor stroma to recruit and proliferate in in vivo transplant tumor models of melanoma (15), breast carcinoma (17), colorectal carcinoma (39), and lung carcinoma (40).…”
Section: Discussionmentioning
confidence: 99%
“…The methods for isolating and propagating the primary human prostate stromal cells used in this study were described previously (isolates PSC27, PSC31, and PSC36; ref. 14). Briefly, tissues from benign areas of radical prostatectomy specimens were collected under approval by the institutional review board.…”
Section: Methodsmentioning
confidence: 99%